Hemoglobin Level Overview Using the Point of Care Test (POCT) Method For Pregnant Women - Annisa Putri, Wakhdaniya; Kristianingrum, Dhita Yuniar; Fatoni, Imam; Aini, Inayatul; Shofiyah, Siti (Jurnal Midpro, 2025)
Anemia is a condition where the number of red blood cells or hemoglobin concentration is insufficient to meet the physiological needs of the body. Lack of knowledge about anemia has an influence on the health behavior of expectant mothers in preventing pregnancy anemia. This study aims to identify the hemoglobin levels of expectant mothers at Puskesmas Jatiwates Tembelang Jombang measured using the Point of Care Test (POCT) method. This study used descriptive research. The population of this study were all expectant mothers who checked ANC at Jatiwates Tembelang Jombang Health Center. The sample in this study was a total of 20 expectant mothers. This study uses total sampling technique. The variable in this study is hemoglobin levels with the Point of Care Test (POCT) method in expectant mothers. The method used is the Point of Care Test (POCT). The results of the examination of hemoglobin levels in expectant mothers are that some respondents have normal hemoglobin levels (50%), almost some respondents have low hemoglobin levels (35%), and few respondents have high hemoglobin levels (15%). The conclusion of this study is that half of the respondents have normal hemoglobin levels, almost half of the respondents have low hemoglobin levels and few respondents have high hemoglobin levels.